2019
DOI: 10.1111/jvec.12342
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of triatomine (Hemiptera: Reduviidae) vectors of Chagas disease in the state of Hidalgo, Mexico

Abstract: Chagas disease represents a significant public health problem in Mexico. In the state of Hidalgo, studies on the presence of triatomines are scarce and restricted to a few locations. To determine the risk of transmission in the state of Hidalgo and stratify the vector potential, the distribution of Triatominae was surveyed from 2015 to 2016 in collaboration with primary health care services and local communities. A total of 570 specimens was collected in 278 houses in 25 municipalities. The species of Triatomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…In the state of Hidalgo, the presence of four Triatominae species has been reported, all naturally infected with T. cruzi (Salazar-Schettino et al 2010, Antonio-Campos et al 2019). Recently, the presence of a single specimen of T. pallidipennis was reported in the state (Chico-Avelino et al 2022), but it was not collected again until two years later.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the state of Hidalgo, the presence of four Triatominae species has been reported, all naturally infected with T. cruzi (Salazar-Schettino et al 2010, Antonio-Campos et al 2019). Recently, the presence of a single specimen of T. pallidipennis was reported in the state (Chico-Avelino et al 2022), but it was not collected again until two years later.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the infection rate have reported to be 41.9% for Colima state and 51.4% in Michoacán state (Espinoza-Gómez et al 2002; Martínez-Ibarra et al 2011), but the infection percentage found in this study is low, similar to that reported for Morelos state with 7% for the peridomestic area (Bautista et al 1999). The low percentage of infection does not mean that there is no risk of transmission of T. cruzi to the population, the probability may be reduced, but the presence of infected patients in the Guadalupe community, and other infections with triatomine species such as T. mexicana (Antonio-Campos et al 2019), may increase the probability of exposure to the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical control campaigns have considerably reduced the prevalence of the disease due to this species vector. Therefore, in 2011, all previously endemic countries of Central America have been certified as free of Chagas disease transmission occurring due to R. prolixus (Hashimoto and Schofield, 2012), but it has been reported again in Mexico in 2019 (Antonio-Campos et al, 2019). R. prolixus is considered as fully domiciliated, but some researchers described the sylvatic populations of R. prolixus in Venezuela (Sanchez-Martin et al, 2006;Feliciangeli et al, 2007;Fitzpatrick et al, 2008) and Colombia (Guhl et al, 2009;Rendón et al, 2015).…”
Section: Introductionmentioning
confidence: 99%